Whole‐genome copy number and immunohistochemical analyses on surgically resected intracholecystic papillary neoplasms. Issue 12 (13th October 2021) - Fujisawa, Mia; Matsushima, Masashi; Carreras, Joaquim; Hirabayashi, Kenichi; Y. Kikuti, Yara; Ueda, Takashi; Kaneko, Motoki; Fujimoto, Ryutaro; Sano, Masaya; Teramura, Erika; Monma, Makiko; Nakae, Hirohiko; et al.
Abstract: Intracholecystic papillary neoplasms are newly defined precancerous lesions. According to Classification of the World Health Organization, they have four histological morphologies, which are biliary, gastric, intestinal, and oncocytic. This study evaluated 17 patients with resected intracholecystic papillary neoplasms in terms of histological, immunohistochemical, and copy number variation (CNV). The histological subtypes included 5 cases of low‐grade (5 gastric) and 12 cases of high‐grade (6 gastric and 6 biliary) neoplasms. Most cases showed high expression of MUC1, MUC5AC, and CK7, moderate expression of MUC6 and Ki‐67, and low expression of CK20, MUC2, and CDX2. The CNV profile identified gain of 7q in 12%, and loss of 1p (18%), 5q (29%), 9p (35%), 12p (17%), 17p (24%), and 19p (18%). No CNVs were observed in low‐grade neoplasms, whereas high‐grade ones had increasing abnormalities. β‐catenin was often expressed in the nucleus of neoplasms with gastric morphology, suggesting the involvement of the Wnt/β‐catenin pathway. However, it was not expressed among those with biliary morphology, which instead exhibited high p53 expression. Neoplasms with biliary morphology showed more CNV changes (9p, 17p, 19p losses). Distinct immunological and CNV patterns were seen in both morphologies, suggesting differences in their pathogenesis. More CNVs accumulated with tumor progression.